Penerapan Prosedur Stock Opname Persediaan Pada Outlet Lawang Agung Kabupaten Gresik - Tasya Belinda Permatasari; Oryza Tannar (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
To ensure stock availability, PT Usaha Utama Bersaudara carries out stock taking in every warehouse and shop. This research focuses on the implementation of stock taking procedures at the Lawang Agung shop, Gresik Regency, whether they are in accordance with the company's standard procedures or not. The author means that the implementation of stock taking is in accordance with the standard procedures set by PT Usaha Utama Bersaudara and there is no difference in the number of goods in the ERP system and the physical inventory at the Lawang Agung shop, Gresik Regency.